Dielectric properties of human skin in vivo in the frequency range 20-38ghz / Najihah Mohd Tamyis - Mohd Tamyis, Najihah (2006)
The increasing use of microwave and millimeter-wave radiation in communications and radar, neces sitates more understanding of dielectric properties of various human tissues for evaluation of potential hazards to human s. In this research , the dielectric properties of human skin in vivo were measured in the frequency range of 20 - 38 GHz. Complex reflection coeffici ents were measured by pressing the palm region of human skin in vivo against a waveguide sensor which consists of coaxial cables, coaxial-to-rectangular waveguide transition and Teflon ™ impedance transformer. Complex permittivities (E*) are calculated from complex reflection coefficients (Sll) by implementing a formulation of an open-ended rectangular waveguide radiating in to the half-space of lossy dielectric material. Results are reported for 42 healthy volunteers which are in the age group of 19 to 40 years. This research also provides experimental design according to the protocol guidelines given by Universiti Teknologi Mara (UiTM) ethics committee. A research protocol was under con sideration of Medical Research and Ethics Committee of the Ministry of Health , Malaysia from June 2003 to May 2004. Since June 2004 , a modified version of the protocol was under consideration by the UiTM Medical Research Ethics Committee and only been approved on April 2005 . This is the first reported result of human skin in vivo in the frequency range of 20 - 38 GHz with statistically significant number of volunteers (42 people from Malay cohort) in the age group of 19 - 40 years. As per protocol , complex reflection coefficient data were measured. Then , complex permittivities, attenuation coeffic ients and emm isivit ies were calculated in the 20 - 38 GHz frequency range. Statistical analysis was performed on the complex permittivity, skin depth and emmisivity data. Then, mean values , standard deviations values and 95% confidence interval values are reported at 15 chosen frequencies in the 20 - 38 GHz rang e.